2018
DOI: 10.3390/rs10091424
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Forest above Ground Biomass Estimation Using Multi-Temporal C-band Sentinel-1 and Polarimetric L-band PALSAR-2 Data

Abstract: Synthetic Aperture Radar (SAR), as an active sensor transmitting long wavelengths, has the advantages of working day and night and without rain or cloud disturbance. It is further able to sense the geometric structure of forests more than passive optical sensors, making it a valuable tool for mapping forest Above Ground Biomass (AGB). This paper studies the ability of the single- and multi-temporal C-band Sentinel-1 and polarimetric L-band PALSAR-2 data to estimate live AGB based on ground truth data collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 43 publications
2
51
1
Order By: Relevance
“…This revealed that HV backscatter was more helpful than HH to model forest productivity, which was consistent with previous findings of aboveground biomass [110,111]. The extinction coefficients modeled by WCM models in this study were much larger than previous studies in modeling aboveground biomass with backscatters and without mosaic [55,97]. This resulted in a relatively less accuracy of stand volume among five forest parameters.…”
Section: Understanding Forest Parameters With Remote Sensing Predictorssupporting
confidence: 88%
See 2 more Smart Citations
“…This revealed that HV backscatter was more helpful than HH to model forest productivity, which was consistent with previous findings of aboveground biomass [110,111]. The extinction coefficients modeled by WCM models in this study were much larger than previous studies in modeling aboveground biomass with backscatters and without mosaic [55,97]. This resulted in a relatively less accuracy of stand volume among five forest parameters.…”
Section: Understanding Forest Parameters With Remote Sensing Predictorssupporting
confidence: 88%
“…The prerequisite assumption of WCM was that the dielectric constant of dry vegetation matter was much smaller than that of the water content of vegetation, and almost all volume backscatters were composed of air in the vegetation canopy [96]. Therefore, WCM was developed assuming that the canopy "cloud", called the water cloud, contained identical water droplets showed the random distribution within the canopy [55]. In this study, the WCM was adopted for the initial exploration [97], which was written as Equation (2):…”
Section: Spatial Modeling Of Stand Volume and Forest Age By Random Fomentioning
confidence: 99%
See 1 more Smart Citation
“…The outputs were backscatter images at 20 m resolution. In this study, only VH polarization images were included in the modeling scheme since it has been shown to be more efficient than VV and HH for the AGB estimation because it is less influenced by soil moisture [71]. The three date data were averaged to generate a mean VH polarization image.…”
Section: Satellite Data Acquisition and Preprocessingmentioning
confidence: 99%
“…This polarization type could influence the backscatter value of vegetation. Difference polarization type of Sentinel-1 can be used to estimate the AGB value [5] [8] . The advantages of using Sentinel-1 images are easily accessed and free to use.…”
Section: Introductionmentioning
confidence: 99%